A Study of Motor Functional Asymmetry Indicators in Different Sportsmanship Level Esports Athletes - Рiatysotska Svitlana; Podrіgalo Leonid; Romanenko, Vyacheslav; Yefremenko, Andrii; Petrenko, Yuliia; Poltoratska, Hanna (Physical Education Theory and Methodology, 2023)
Purpose. to research and analyze of the indicators of functional asymmetry in different sportsmanship level esports athletes. Methods. the study involved 20 middle-aged athletes (18±1.53) years old, divided into groups according to their sportsmanship. Group 1: elite players of semi-professional teams in CS:GO and DOTA 2 disciplines, n=10, age (19.2±0.50) years. Group 2: amateur CS:GO and DOTA 2 players, n=10, age (18.2±1.04) years. The functional asymmetry of the movements of the upper limbs was determined using a special program for tablet computers running iOS, developed at the departments of martial arts, computer science and biomechanics of the KhSAPC. Results. It has been established that in terms of the number of clicks per unit of time, elite esports athletes are dominated by amateurs by 5.54% on the left and 5.14% on the right hand; in terms of visual motor reaction time, elite esports athletes prevail by 5.54% on the left hand and 5,07% on the right hand; elite esports athletes showed a 13.3% shorter left-hand click duration, but amateurs showed a 6,83% shorter right-hand click duration. Conclusions. Players with a higher level of preparedness tend to have less asymmetrical movements. In the proposed test, elite athletes demonstrate a greater number of movements per unit of time; at the 2nd stage of testing, the differences are significant (p<0.05). At the same time, the reaction time of more skilled players is less than that of amateurs; at the 2nd and 4th stages of the test, the differences are significant (p<0.05). Indicators of functional asymmetry of movements of the upper limbs informatively characterize the level of preparedness of esports athletes and can be included in the program for monitoring the physical condition of players in cybersport.